Correlation of local impedance, global impedance and contact force with resulting lesion size in RF ablation. (19th May 2022) - Wachter, A; Bahlke, F; Popa, M; Foerschner, L; Krafft, H; Maurer, S; Telishevska, M; Englert, F; Lengauer, S; Kottmaier, M; Lennerz, C; Reents, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: During clinical application of RF-energy, several parameters are constantly observed, e.g. RF time, power, global impedance and temperature. The new parameter "local impedance" is gaining importance and might be a possible real-time marker for predicting long-lasting RF-lesions and increasing safety. The aim of this study was to investigate the correlation between local and global impedance as well as RF power and contact force. Methods: RF-lesions were created using an ex vivo model with porcine cardiac preparations. These were put in a saline-filled container with a dispersive electrode. Global impedance was held at 120 Ohm by adjusting saline and water. Additionally, a heated thermostat and a circulation pump were installed to imitate blood flow. RF-lesions were produced with different settings of energy and contact force (20, 30, 40 and 50 watts; contact force of 0-5g, 10-15g and 20-25g). While creating the lesions, global and local impedance, temperature, energy and RF time were documented, as well as the current lesion width and depth. Local and global impedance drops were calculated as the difference between baseline impedance and current impedance. Results: In total, 1223 measurements were made during application of RF-energy. 6 steam pops occurred. Contact force, local and global impedance changes showed highly significant correlations with lesion depth and diameter. Amongst analyzed values, local impedance drop showed highest correlation with lesion diameter and depth (r = 0, 391 and 0, 613; p<0, 001). Visualized in Figure 1 and 2, global and local impedance correlate with lesion diameter and depth. Discussion: Local impedance was found to be a suitable real-time marker for lesion size, showing significantly higher correlations with RF lesion size than contact force and global impedance. Further investigation is necessary to find a cut off for a safe but long-lasting RF-lesion.